Li and Fa in Contract Law from the Perspective of Chinese Legal Philosophy - Putro, Widodo Dwi; Tanya, Debora Jessica Desideria; Martini, Dwi (Lex Scientia Law Review, 2024)
Traditional Chinese law is strongly influenced by two schools of thought, namely Confucianism which emphasizes “rule by li” and Legalism which emphasizes “rule of fa”. Both schools of thought have different accentuations, specifically, “li” emphasizes trust, while “fa” prioritizes certainty. In light of this ambivalence, this research seeks to address the following problem formulation: (i) how do the principles of "li" and "fa" inform the foundation of legal agreements? (ii) how has the evolution of these principles been shaped by Mainland Chinese and Peranakan Chinese communities? To address these inquiries, this study delves into the influence of "li" and "fa" within contract law, specifically within the context of Contract Law among Mainland Chinese and Peranakan Chinese in Indonesia. The researcher conducts an exploration of the Analects of Confucius to elucidate the essence of "li" and delves into the texts of Shang Yang and Han Fei Zi to discern the essence of "fa." The findings of this research are subsequently employed as a foundation for analyzing the impact of "li" and "fa" on legal practices in Mainland Chinese and Peranakan Chinese societies, viewed through the lens of legal philosophy.